2002
DOI: 10.1080/00498250210144811
|View full text |Cite
|
Sign up to set email alerts
|

Permissive and suppressive effects of dexamethasone on enzyme induction in hepatocyte co-cultures

Abstract: 1. Steroids are known to act as permissive factors in hepatocytes. This study shows that dexamethasone (DEX) is a permissive factor for induction of CYP2B1/2, CYP3A1, CYP2A1 and probably also CYP2C11 in cultures with primary rat hepatocytes. 2. The induction factor of phenobarbital (PB)-induced formation of 16beta-hydroxytestosterone (OHT), a testosterone biotransformation product predominantly formed by CYP2B1, is increased 18-fold by the addition of 32 nM DEX to the culture medium. Interestingly, higher conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…In rat hepatocytes, it was shown that addition of DEX (100 nM) to the medium increased the inducibility of CYP2B (Ringel et al, 2002). In the present study in colon but not in small intestinal slices, DEX appeared to enormously induce CYP2B15 mRNA.…”
Section: Discussionmentioning
confidence: 49%
“…In rat hepatocytes, it was shown that addition of DEX (100 nM) to the medium increased the inducibility of CYP2B (Ringel et al, 2002). In the present study in colon but not in small intestinal slices, DEX appeared to enormously induce CYP2B15 mRNA.…”
Section: Discussionmentioning
confidence: 49%
“…This result could be due to the relatively short incubation time chosen in our studies (24 h). Induction of DMEs has been shown to be dependent on the concentration of the inducer and incubation period (Jigorel et al, 2006), on the presence of supplements in the incubation medium (Ringel et al, 2002), and also on the type of cell line used (Hartley et al, 2006). Therefore, "falsenegative" results could be explained by these factors.…”
Section: Induction In Human Intestinal Slicesmentioning
confidence: 97%
“…Nevertheless, it is well known that some specific situations (i.e., stress, immunological response, pathologic conditions) can modulate the expression of CYP3A. Moreover, DEX has been demonstrated to have either a permissive or a repressive effect on several CYP isoforms, sometimes depending on the dose used (Iber et al, 1997;Ringel et al, 2002). CYP3A expression was never affected by the treatment in the other experiments cited above and executed in poultry and meat cattle (Nebbia et al, 1996;Cantiello et al, 2002;Capolongo et al, 2004;Merlanti et al, unpublished;Dacasto et al, unpublished).…”
Section: Cyp3amentioning
confidence: 98%